INTERSTITIAL LUNG DISEASE AND BULLOUS PEMPHIGOID ASSOCIATED WITH DIRECT ORAL ANTICOAGULANT USE: A CASE REPORT OF LITERATURE-BASED PHARMACOVIGILANCE SIGNAL DETECTION - Hadži-Nikolić, Nikica (Srpski medicinski časopis Lekarske komore, 2025)
Introduction/Objective: Direct oral anticoagulants (DOACs) have significantly improved the prevention and management of thromboembolic disorders owing to predictable pharmacokinetics, simplified dosing, and reduced monitoring compared to vitamin K antagonists. However, as clinical use increases, emerging evidence suggests that DOACs may also cause rare but clinically important non-hemorrhagic adverse events, such as interstitial lung disease (ILD) and bullous pemphigoid (BP). The aim of this study is to present and evaluate drug safety signal cases reported in the existing literature and to contextualize them in order to enhance clinician awareness of rare pulmonary and dermatologic adverse events associated with DOAC therapy. Case report: This report describes signal detection of ILD in 11 elderly male patients following exposure to apixaban, dabigatran, or edoxaban, with latency periods ranging from several days to four years. Most patients showed clinical improvement following drug discontinuation and corticosteroid therapy; however, two experienced fatal outcomes. We additionally report a signal detection case of rivaroxaban-associated bullous pemphigoid in an 86-year-old male with multiple comorbidities, who fully recovered following rivaroxaban withdrawal and corticosteroid therapy, with no recurrence after one year of treatment with apixaban. Conclusion: Prompt recognition and management are crucial for favorable outcomes. These cases underscore the importance of pharmacovigilance and the need for continued investigation to elucidate mechanisms and risk factors for such reactions.